Are Nutraceuticals Beneficial in Chronic Kidney Disease? - Jacek Rysz; Beata Franczyk; Krzysztof Kujawski; Izabela Sacewicz-Hofman; Aleksanda Ciałkowska-Rysz; Anna Gluba-Brzózka (MDPI AG, 2021)
Chronic kidney disease (CKD) is a worldwide health problem in which prevalence is constantly rising. The pathophysiology of CKD is complicated and has not been fully resolved. However, elevated oxidative stress is considered to play a vital role in the development of this disease. CKD is also thought to be an inflammatory disorder in which uremic toxins participate in the development of the inflammatory milieu. A healthy, balanced diet supports the maintenance of a good health status as it helps to reduce the risk of the development of chronic diseases, including chronic kidney disease, diabetes mellitus, and hypertension. Numerous studies have demonstrated that functional molecules and nutrients, including fatty acids and fiber as well as nutraceuticals such as curcumin, steviol glycosides, and resveratrol not only exert beneficial effects on pro-inflammatory and anti-inflammatory pathways but also on gut mucosa. Nutraceuticals have attracted great interest recently due to their potential favorable physiological effects on the human body and their safety. This review presents some nutraceuticals in which consumption could exert a beneficial impact on the development and progression of renal disease as well cardiovascular disease.